2019
DOI: 10.1002/pmic.201800446
|View full text |Cite
|
Sign up to set email alerts
|

OLFM4 Expression in Ductal Carcinoma In Situ and in Invasive Breast Cancer Cohorts by a SWATH‐Based Proteomic Approach

Abstract: Human olfactomedin‐4 (OLFM4) is a secreted protein involved in a variety of cellular functions including proliferation, differentiation, apoptosis, and cell adhesion. OLFM4 expression has been studied in several tumor types including gastric, colorectal, lung, and endometrioid cancers where it has been suggested to be an independent favorable or unfavorable prognostic marker. For breast cancer, the clinical significance of OLFM4 is still unclear. In the present study, SWATH‐MS is used as a tool for the robust … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Subsequently, this list of 130 candidates was crossed with experimental data collected on rat malignant mesotheliomas (MMs) differing by their invasiveness (21), and then with clinical data from cohorts of patients with colon adenocarcinoma (22) or breast cancer (23). As a result of technological improvements that occurred between these two studies, the number of specific biomarkers identified in breast cancer was higher than that in colon cancer.…”
Section: Data Collection Methodsmentioning
confidence: 99%
“…Subsequently, this list of 130 candidates was crossed with experimental data collected on rat malignant mesotheliomas (MMs) differing by their invasiveness (21), and then with clinical data from cohorts of patients with colon adenocarcinoma (22) or breast cancer (23). As a result of technological improvements that occurred between these two studies, the number of specific biomarkers identified in breast cancer was higher than that in colon cancer.…”
Section: Data Collection Methodsmentioning
confidence: 99%
“…For treatment with trypsin, desalting, and peptide analysis, ultrapure water (Purelab Option-Q, 18.2 MΩ.cm, VWR International S.A.S., Fontenay-sous-Bois, France) was used during all procedures. See legends to Supplementary Table S1 and reference [68] for additional informations on sample preparation of human tumor samples.…”
Section: Sample Preparation For Swath-ms Analysismentioning
confidence: 99%
“…We then used mass spectrometry analysis to understand how p21 maintains senescence besides its well-known function as a cdk inhibitor. To this end, this protein was inactivated in senescent cells, extracts were collected after 48 hr and analyzed by SWATH-MS approaches as we recently described (20). GSEA analysis indicated that Myc and E2Fs proliferative pathways were reactivated as expected.…”
Section: Mtor Inhibition Prevents Cis Escapementioning
confidence: 98%